Lexical semantic characteristics of Arabisms in Uzbek and English languages - Divanova, Mohira Husanovna (Science and Education, 2023)
This article discusses the expression of lexical semantic features of Arabisms in Uzbek and English languages. Information about the use of Arabicisms in linguistics is also provided.